PENINGKATAN JUMLAH KELAHIRAN ANAK BABI MELALUI TEKNOLOGI INSEMINASI BUATAN DI DESA TAKMUNG KLUNGKUNG - SUMARDANI NLG; ARTININGSIH NM; SUBERATA IW (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2010)
ABSTRACT The short course of using Artificial Insemination (AI) on swine was conducted on October 30th 2009 at Takmung Village, Bajarangkan District, Regency of Klungkung. There were 25 farmers who merged into group of livestock ‘Semadhi Karya’ as participants of this activity. The aimed of this activity was to increase litter size of swine with AI program. The methods of activity were : giving counseling about management of animal husbandry in breeding farm, AI program, and then practising inseminate on five of swine. Based on the process of short course it can be concluded that, the response of participants on AI was very enthusiastic in joining the activity.